ROBERT DAHL’S CONCEPT OF POLITICAL EQUALITY: THE BEDROCK OF ENDURING DEMOCRACIES - Okwa, Felix Agbo (African Journal of Social and Behavioural Sciences, 2025)
Robert Dahl made a significant contribution to the theory of democracy in the twentieth century. His central claim is that every citizen is substantial in that each person’s preference ought to carry equal weight in the processes of governance. He calls this idea political equality. This paper explores Dahl’s concept of political equality as the moral and institutional foundation of enduring democracies. To this end, the paper argues that political equality is not merely a procedural norm but rather a substantive condition for the actualization of democratic legitimacy and stability. The paper achieves this by examining how political equality ensures inclusive participation, responsive leadership, and the continuous renewal of democratic trust. In furtherance of this, the paper critiques contemporary democratic systems where economic inequality, elite capture, and information divide have made the principle of equal political voice improbable. Using the analytic method of philosophical research, the study highlights that democracies endure only when they institutionalize mechanisms that protect citizens from marginalization and ensure equitable distribution of political power. Consequently, the paper concludes that the revitalization of political equality in both established and emerging democracies is indispensable for preventing democratic regression and fostering civic solidarity in plural societies. Hence, Dahl provides an enduring moral compass for reconceiving democratic practice in contemporary times.